Genital Paget's disease with general metastasis a case report - Okuno, H (Hinyokika kiyo. Acta urologica Japonica, 1988)
A 74-year-old man with the chief complaint of ulceration of penile shaft and scrotal swelling was referred to our hospital on November 7, 1985. Biopsy specimen of the local lesion histologically revealed invasive adenocarcinoma with Paget's cell. Clinical studies revealed a high serum carcinoembryonic antigen (CEA) level and regional lymph node metastasis was highly suspected. We concluded that the patient was suffering from Stage II genital Paget's disease. Emasculation, bil-inguinal and pelvic lymph node dissection, and free skin mesh grafting were performed on December 24, 1985. Histological findings of the tumor confirmed Paget's disease and bil-inguinal and pelvic lymph node metastases. CEA staining showed CEA positive malignant cells in both the primary lesion and metastatic lymph nodes. After operation, the rapid deterioration of the patient's condition was accompanied by extremely high serum CEA levels, obstructive jaundice, and evidence of metastasis to the liver. He died 24 days after operation and autopsy could not be performed. We recommend aggressive treatment when clinical studies reveal invasion to the epidermis, high serum CEA levels and lymph node metastasis